Red blood cell-tumor cell interactions promote tumor cell progression - Thais Pereira-Veiga; Celso Yáñez-Gómez; Aleksi Pekkarinen; Carmen Abuín; Christine Blechner; Miriam González-Conde; Christian Mess; Sabine Vidal-y-Sy; Ayham Moustafa; Bente Siebels; Ana B. Dávila-Ibáñez; Pablo Cabezas-Sainz; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract A critical step in the metastatic cascade is the survival of circulating tumor cells (CTCs) within the bloodstream. Although interactions between CTCs and various hematopoietic cells have been described, the role of red blood cells (RBCs) remains underexplored. This study investigated the interactions between tumor cells and RBCs from breast and lung cancer patients, revealing significant phenotypic and functional changes in tumor cells, unlike interactions with RBCs from healthy donors. Tumor cell and patient-derived RBC co-cultures increased tumor cell attachment and induced morphological changes. RBC-primed tumor cells showed increased adhesion, disruption of the endothelial barrier, and invasiveness, both in vitro and in vivo. Global proteome changes, including actin remodeling and VASP accumulation at cell edges, promote directional migration. RBCs from patients with metastatic breast cancer also upregulate PAK4, enhancing migration and epithelial-mesenchymal transition, whereas PAK4 inhibition reduces these effects. Clinically, a higher red blood cell distribution width (RDW) in patients with metastasis is associated with increased CTC counts and poor outcomes. This study highlights the previously unrecognized role of RBCs in promoting metastatic behavior in cancer cells and suggests potential therapeutic targets, such as PAK4, to counteract these effects.